2015
DOI: 10.3349/ymj.2015.56.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Various Applications of Deep Temporal Fascia in Rhinoplasty

Abstract: PurposeIn Asians, nasal dorsal and tip augmentation procedures are usually performed at the same time, and most dorsal augmentations use implants. In this study, dorsal augmentation was given by various types of grafts using deep temporal fascia (DTF) for primary rhinoplasty cases using only autologous tissues to improve the curve of hump noses and depressions. For secondary rhinoplasty cases, DTF was used to improve implant demarcation and transparency. Such effectiveness and utility of DTF is discussed.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…However, the results of various studies have shown that a number of patients undergoing rhinoplasty required reoperation to resolve the anatomic and aesthetic drawbacks for a variety of reasons, and in a significant number of patients, the nasal dorsum reconstruction was the only way for the nose regeneration. [15][16][17][18] Consequently, using the diced cartilage wrapped by temporal fascia and alloderm are two commonly used methods, and the effect of both methods on the nasal dorsum resconstruction has been reported to be favorable, but the results of our study showed that using the temporal fascia covering was associated with the greater patient's satisfaction and more favorable height of the nasal dorsum. The use of diced cartilage greatly enhances the range of agmentation with autologous cartilage and is currently the preferred method for many surgeons.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, the results of various studies have shown that a number of patients undergoing rhinoplasty required reoperation to resolve the anatomic and aesthetic drawbacks for a variety of reasons, and in a significant number of patients, the nasal dorsum reconstruction was the only way for the nose regeneration. [15][16][17][18] Consequently, using the diced cartilage wrapped by temporal fascia and alloderm are two commonly used methods, and the effect of both methods on the nasal dorsum resconstruction has been reported to be favorable, but the results of our study showed that using the temporal fascia covering was associated with the greater patient's satisfaction and more favorable height of the nasal dorsum. The use of diced cartilage greatly enhances the range of agmentation with autologous cartilage and is currently the preferred method for many surgeons.…”
Section: Discussionmentioning
confidence: 57%
“…The possible justification for the poorer results of using the alloderm is probably because of the more inflammatory reaction relative to the temporal fascia that is an autogenous tissue, and eventually led to greater absorption and irregularity following the use of alloderm for wrapping the diced cartilage. [15][16][17][18] Further, the penetration and permeability rates can be considered as the possible causes. Therefore, although the use of temporal fascia causes more time spent for the surgery and is associated with the morbidity of the donor area, the application results are more reliable, and hence, it is recommended to be preferably used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cartilage grafts for nasal dorsum contour seemed to be good at the time of the implant, but in thin-skinned individuals, as the skin gets thinner with age, the surface at the graft margin was reported to be apparent within 16 months after rhinoplasty. Therefore, an additional covering layer (usually a temporal fascia graft) is required, which will be placed under the skin and over the cartilage graft in order to bolster the thickness of the skin, minimize unwanted visible contour irregularities, and create natural aesthetic lines (Shiffman and Di Giuseppe, 2013;Ishii, 2014;Park et al, 2015). The temporal fascia grafts are fairly thin (from 1.60 to 1.90 mm), resulting in a successful and long-lasting dorsal contouring in rhinoplasty (Shiffman and Di Giuseppe, 2013).…”
Section: Gapdhmentioning
confidence: 99%
“…In rhinoplasty, the deep temporal fascia (DTF) is among the most important autologous graft materials used for various purposes. The DTF is generally utilized alone or as a fascia-wrapped cartilage graft in soft tissue reinforcement in reconstructive rhinoplasty [1,2] and for radix augmentation, correcting dorsal skin irregularities, and reinforcing the tip skin in aesthetic rhinoplasty [3][4][5]. Since the DTF is harvested from the same surgical field as rhinoplasty and features lower donor site morbidity rates, the DTF has advantages over other autologous tissues such as dermofat tissue [6], tensor fascia lata [7], and mastoid fascia [8].…”
Section: Introductionmentioning
confidence: 99%